2020
DOI: 10.3389/fphar.2020.01251
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Depressive Effects of Hesperidin and the Relative Mechanisms Based on the NLRP3 Inflammatory Signaling Pathway

Abstract: There is increasing evidence showing that inflammation is associated with depression in humans. Hesperidin, a natural bioflavonoid, has performed excellent effects on depression. The aim of this research was to investigate the therapeutic effect of hesperidin on chronic unpredictable mild stress (CUMS)-induced rats. The sucrose preference test (SPT), forced swimming test (FST), and open field test (OFT) were performed to measure the depression-related symptoms. The enzyme-linked immunosorbent assay (ELISA) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Due to long-term exposure stress, high incidence rate, and severe economic burdens, depression has attracted global attention in recent years ( Beurel et al, 2020 ). Chronic stress can lead to low-grade inflammatory reaction, cell-mediated immune activation, and so on, and then lead to abnormal nerve conduction and brain functional network disorder, which are closely related to the occurrence of depression ( Franklin et al, 2018 ; Xie et al, 2020 ; Xie et al, 2021 ). At present, although many studies focus on the molecular imaging mechanism and drug treatment of depression, there are still no specific targeted drugs and compound preparations for depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to long-term exposure stress, high incidence rate, and severe economic burdens, depression has attracted global attention in recent years ( Beurel et al, 2020 ). Chronic stress can lead to low-grade inflammatory reaction, cell-mediated immune activation, and so on, and then lead to abnormal nerve conduction and brain functional network disorder, which are closely related to the occurrence of depression ( Franklin et al, 2018 ; Xie et al, 2020 ; Xie et al, 2021 ). At present, although many studies focus on the molecular imaging mechanism and drug treatment of depression, there are still no specific targeted drugs and compound preparations for depression.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of IL-1β, IL-6, TNF-α, and CRP in peripheral blood of MDD patients were significantly increased (Haapakoski et al, 2015;Liu et al, 2017;Felger et al, 2020), and the levels of inflammatory factors in cerebrospinal fluid were abnormal (Haapakoski et al, 2015). At the same time, the expression of inflammatory factors in different tissues of depression animal model also increased (Pan et al, 2014;Zhang et al, 2015;Xie et al, 2020). Moreover, depression is closely related to inflammation damage-associated molecular patterns (DAMPs) Xie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have confirmed that HDN attenuates inflammatory responses in I/R injury ( 9 , 17 ). In a chronic unpredictable mild stress (CUMS)-induced rat model, Xie et al ( 37 ) found that HDN treatment significantly relieved depressive-like behaviors in CUMS rats by decreasing the expression levels of IL-6 and TNF-α in the prefrontal cortex and microglia. In addition, they found that the relative mechanisms were based on the NLR family pyrin domain containing 3 inflammatory signaling pathway ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a chronic unpredictable mild stress (CUMS)-induced rat model, Xie et al ( 37 ) found that HDN treatment significantly relieved depressive-like behaviors in CUMS rats by decreasing the expression levels of IL-6 and TNF-α in the prefrontal cortex and microglia. In addition, they found that the relative mechanisms were based on the NLR family pyrin domain containing 3 inflammatory signaling pathway ( 37 ). Heo et al ( 38 ) revealed that HDN treatment in rats with spinal cord injury reduced neuropathological changes (includinghemorrhage, inflammatory cell infiltration, and tissue loss) and levels of proinflammatory cytokines, such as TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…It reduces the depressive symptoms by modulating the kappa-opioid and serotonergic 5-HT 1A receptors [3]. HESP antidepressant effect was demonstrated on mice exposed to chronic unpredictable mild stress [10]. Based on its powerful memory-enhancing and antioxidant benefits, it has the potential to be used as a treatment for Alzheimer's disease and dementia.…”
Section: Introductionmentioning
confidence: 99%